Can exercise-induced muscle damage be related to changes in skin temperature?. (30th October 2018) - da Silva, Willian; Machado, Álvaro S; Souza, Mauren A; Kunzler, Marcos R; Priego-Quesada, Jose I; Carpes, Felipe P
Abstract: Objective : Measurement of skin temperature using infrared thermography has become popular in sports, and has been proposed as an indicator of exercise-induced muscle damage after exercise. However, the relationship between skin temperature and exercise-induced muscle damage is still unclear. Here we set out to investigate the relationship between skin temperature and exercise-induced muscle damage. Approach : Twenty untrained participants completed a protocol of exercise for calf muscles. Before and after exercise blood samples were collected to determine creatine kinase and acetylcholinesterase activity. Thermal images were recorded from the exercised muscles to determine skin temperature. Delayed onset muscle soreness was quantified. Correlations between skin temperature and exercise-induced muscle damage were analyzed considering thermal data, creatine kinase and acetylcholinesterase activity at different time moments. Main results : We found delayed onset muscle soreness and an increased creatine kinase activity 48 h after exercise ( P   <  0.01). Skin temperature parameters (average, maximal, amplitude and difference pre- and post-exercise, immediately after and 48 h after) did not correlate with the creatine kinase responses ( P   >  0.05). Acetylcholinesterase activity remained stable ( P   =  0.59). Significance : We recommend caution when considering changes in skin temperature as dependent on the level of localized and symmetric muscle damage considering calf muscles in untrained participants.